2019
DOI: 10.1111/cmi.13064
|View full text |Cite
|
Sign up to set email alerts
|

StreptococcalsagAactivates a proinflammatory response in mast cells by a sublytic mechanism

Abstract: Mast cells are implicated in the innate proinflammatory immune defence against bacterial insult, but the mechanisms through which mast cells respond to bacterial encounter are poorly defined. Here, we addressed this issue and show that mast cells respond vividly to wild type Streptococcus equi by up‐regulating a panel of proinflammatory genes and by secreting proinflammatory cytokines. However, this response was completely abrogated when the bacteria lacked expression of sagA, whereas the lack of a range of ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 52 publications
(106 reference statements)
0
23
0
Order By: Relevance
“…The contribution of SLS to the pathogenesis of streptococcal necrotizing soft tissue infection by S. pyogenes and Group G streptococci was also reported 133 . Moreover, the p38 and Erk1/2 signaling pathways induced by SLS were found to play a central role in the proinflammatory response of mast cells against S. equi 134 …”
Section: Slsmentioning
confidence: 87%
“…The contribution of SLS to the pathogenesis of streptococcal necrotizing soft tissue infection by S. pyogenes and Group G streptococci was also reported 133 . Moreover, the p38 and Erk1/2 signaling pathways induced by SLS were found to play a central role in the proinflammatory response of mast cells against S. equi 134 …”
Section: Slsmentioning
confidence: 87%
“…Bacterial recognition by MCs has often been accredited to TLRs 6,9 . However, work by us and others have in addition shown that sublytic levels of bacterial pore-forming toxins can elicit secretion of cytokines, including IL-6, from MCs [14][15][16] . We therefore asked if MC activation by S.Tm could be ascribed to i) classical recognition of bacterial PAMPs, ii) membrane-perturbing effects of the TTSS-1 translocon (in analogy to pore-forming toxins), or iii) alternative mechanism(s).…”
Section: Mast Cells and Salmonella Coexist In The Infected Murine Gutmentioning
confidence: 94%
“…Based on these data, the authors concluded that bacteria-derived SLS at sublytic concentrations is a major stimulus for mast cell activation leading to proinflammatory gene expression and cytokine production. It should be noted, however, that in contrast to CDCs, SLS induced only week degranulation (106). Kramer et al (111) examined the effect of a-hemolysin, a protein toxin that assembles on membranes to form a heptameric pore structure (133).…”
Section: Comparable Response Of Mast Cells To Cdcs and Other Pore-forming Compoundsmentioning
confidence: 99%
“…A recent study showed that BMMCs responded vividly to wild-type S. equi by upregulating a panel of proinflammatory genes and secreting proinflammatory IL-6, TNF-α, and monocyte chemoattractant protein (MCP)1 ( 106 ). However, this response was abrogated entirely in S. equi lacking the sagA gene encoding SLS.…”
Section: Comparable Response Of Mast Cells To Cdcs and Other Pore-forming Compoundsmentioning
confidence: 99%
See 1 more Smart Citation